KERAGAAN PERTUMBUHAN DAN KOMPONEN HASIL BEBERAPA VARIETAS UNGGUL KEDELAI DI ACEH BESAR - Bakhtiar Bakhtiar; Taufan Hidayat; Yadi Jufri (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
Soybean is an important food for national food security. Many soybean varieties have been released by the government, but only few were adopted by farmers. The purpose of this study was to identify superior soybean varieties that are adaptive in Aceh Besar, Aceh Province. The experiment was conducted in Village Limpok, Aceh Besar during dry season in 2013 and arranged in a randomized block design with 3 replications. The result showed that variety Kaba and Detam had very good vegetative growth performance. The fastest flowering varieties were Detam and Burangrang, while variety Gema, Tanggamus, and Orba were the slowest flowering. Variety Kaba and Orba had the highest productive node, while the least was Grobogan. Variety Kaba, Kipas Merah Bireuen, and Orba had the most productive branches, while local variety Bener Meriah and Grobogan had the least productive branches. Grobogan had the greatest seed size, followed by Burangrang and Anjasmoro. Kipas Merah Bireuen and Sinabung had the highest seed weight per plant but having the smallest seeds. Sinabung was the most adaptive in Aceh Besar.